Procuring and Managing Adaptively: 5 Case Studies of Adaptive Mechanisms - Pryor, Tony (USAID Learning Lab, USAID, 2018)
Flexibility in program management is essential in all of the countries where USAID works. This is especially true in non-permissive environments (NPEs), where the ability to learn and adapt quickly to changing circumstances can help USAID staff members achieve their desired outcomes.

USAID ADS 201 - Program Cycle Operational Policy (Update 10/29/2018) - USAID (USAID, 2018)